Surface Measure to Depth (SMeTD): a new low-budget system for 3D water temperature measurements for combining with UAV-based thermal infrared imagery - Eva Loerke; Ina Pohle; David Drummond; Pauline E. Miller; Josie Geris (Environmental Monitoring and Assessment, 2023)
Characterising spatial patterns in water temperature is important for monitoring aquatic habitats and understanding physical and biogeochemical processes to support environmental management decisions. As freshwater bodies exhibit high spatial and temporal variability, high-resolution 3D temperature data are essential to understand local anomalies. The acquisition of simultaneously high spatial and temporal datasets in the field has so far been limited by costs and/or workload associated with commonly used monitoring systems. We present a new, low-cost, spatially and temporally flexible 3D water temperature monitoring system, Surface Measures to Depth (SMeTD). SMeTD can be used to provide information on the relation of water surface temperature to changes with depth, characterise water temperature in 3D and ground truth remotely sensed thermal infrared data. The systems performance was tested under laboratory conditions and under controlled conditions in the field. This revealed an accuracy comparable to established but more expensive monitoring systems. Field testing of SMeTD involved 1-min data collection of 3D water temperature for a full diurnal cycle in a lake. The 3D temperature patterns were supported by a thermal infrared image of the lakes surface. The field dataset demonstrated higher water temperatures and higher water temperature variation at the surface compared to deeper layers. SMeTD can be used to observe a broad range of hydrological processes in natural and artificial aquatic environments and help to understand processes involved with energy budgets, infiltration, limnology, or groundwater surface water exchange.

Long-term daily stream temperature record for Scotland reveals spatio-temporal patterns in warming of rivers in the past and further warming in the future - Eva Loerke; Ina Pohle; Mark E. Wilkinson; Mike Rivington; Douglas Wardell-Johnson; Josie Geris (Science of The Total Environment, 2023)

Bayesian analysis of high-frequency water temperature time series through Markov switching autoregressive models - Luigi Spezia; Sheila Gibbs; Miriam Glendell; Rachel Helliwell; Roberta Paroli; Ina Pohle (Environmental Modelling & Software, 2023)

Management Influences on Stream-Flow Variability in the Past and Under Potential Climate Change in a Central European Mining Region - Ina Pohle; Anne Gädeke; Sabine Schümberg; Christoph Hinz; Hagen Koch (Water Resources Management, 2019)

Challenges of Reducing Phosphorus Based Water Eutrophication in the Agricultural Landscapes of Northwest Europe - Roland Bol; Gerard Gruau; Per-Erik Mellander; Rémi Dupas; Marianne Bechmann; Eva Skarbøvik; Magdalena Bieroza; Faruk Djodjic; Miriam Glendell; Philip Jordan; Bas Van der Grift; Michael Rode; et al. (Frontiers in Marine Science, 2018)

Trend analysis for integrated regional climate change impact assessments in the Lusatian river catchments (north-eastern Germany) - Anne Gädeke; Ina Pohle; Hagen Koch; Uwe Grünewald (Regional Environmental Change, 2017)

Potential impacts of climate change and regional anthropogenic activities in Central European mesoscale catchments - Ina Pohle; Hagen Koch; Tobias Conradt; Anne Gädeke; Uwe Grünewald (Hydrological Sciences Journal, 2015)